MODEL SISTEM INFORMASI PEMBIMBINGAN SKRIPSI ONLINE TERHADAP EFEKTIVITAS PENYELESAIAN SKRIPSI DENGAN METODOLOGI SCRUM - Faza, Riky (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2017)
This research is intended to develop an information system model for online tutoring process, in order to streamline the process of guidance that has been done conventionally, ie lecturers and students meet directly then discuss chapter by chapter every thesis discussion material. the weakness of the conventional way is the limited time and space so that it can inhibit the process of completion of the thesis by students. To facilitate the development of this system we used the notation of UML as an international standard notation in the analysis and design system, and also used Scrum as a software methodology approach in the process of system engineering, which where the scrum has a system of completion of work made in small tasks in supervise and evaluate in the near term so that the progress of the work can be well supervised. By using Nginx Server as the web server, MySQL Server as the database server, PHP Programming Language as the main language for developing it’s application, is expected to bring out the integrations of business process and information flow.